Deskripsi Hasil Belajar Siswa Menggunakan Project Based Learning Pada Mata Pelajaran Dasar-Dasar Kejuruan Fase F - Pebrial Takaendengan (Departement of Mathematics Education, 2023)
This study aims to describe the learning outcomes of class XI students of SMK Negeri 3 Manado in the subject dasar-dasar kejuruan fase F with network concept map material. This research is a descriptive research conducted in the odd semester of the 2022/2023 academic year in November-December 2022 with 12 research subjects. Data was collected through test instruments, namely questions in the form of descriptions and interviews. The results showed that the use of the project based learning model in learning had a positive impact, namely that all students who were included as research subjects were able to achieve and exceed the KKM score for the dasar-dasar kejuruan fase F, namely 80. Furthermore, students who were in the high category had a percentage of 33.33 %, medium category with a percentage of 50% and low category with 16.67%.